Successful management of three-wall periodontal intrabony defect using novabone dental putty® - Roshan Prabhakar Dhonge; Anukriti Vishwakarma (Wolters Kluwer Medknow Publications, 2018)
Chronic periodontitis can result in destructive changes in the soft and hard tissues of the periodontium, culminating in loss of periodontal attachment, formation of periodontal pocket, and loss of supporting alveolar bone. Suprabony pockets are typically associated with a horizontal pattern of alveolar bone loss that is not amenable to periodontal regeneration with available regenerative therapies, while intrabony pockets are associated with vertical or angular bony defects that are often responsive to periodontal regeneration. The purpose of this case report is to describe the regenerative potential of Novabone Dental Putty® in the human periodontal three-wall intrabony defect. The case has been evaluated clinically and radiographically at baseline and 6 months after the completion of osseous regenerative surgery. The successful healing of intrabony defect was found to be achieved after 6 months of follow up.